Convolutional Graph Thermography for Subsurface Defect Detection in Polymer Composites - Liu, Kaixin; Yu, Qing; Liu, Yi; Yang, Jianguo; Yao, Yuan (IEEE transactions on instrumentation and measurement, 2022)
Infrared thermography for quality assessment of polymer composites has gained increasing attention with the development of various thermographic data analysis methods. However, low-quality thermal images containing noise and inhomogeneous backgrounds restrict the defect detection performance of these methods. In this work, a convolutional graph thermography (CGT) method is proposed for subsurface defect detection in polymer composites. With a developed convolutional autoencoder thermogram enhancer, the noise and inhomogeneous background of the thermal image can be reduced. Subsequently, a graph-based dimensionality reduction method performs feature extraction on the enhanced thermograms. Consequently, the low-dimensional intrinsic manifolds of the high-dimensional thermographic data are characterized to highlight the defects visually. Two case studies on carbon fiber reinforced polymers demonstrated the performance of the proposed method.